‘It’s just not worth a damn!: investigating perceptions of the value in attending university - Cook, Steve; Watson, Duncan; Webb, Rob (Taylor & Francis, 2018)
Mass expansion of the UK Higher Education (HE) sector is eroding its well-documented benefits – leading many to question whether HE remains worthwhile. Avoiding the traditional approach of estimating the returns to HE, we investigate why many now feel that attending university will not yield any financial benefits. Using BSA data from 2010 we find that this negativity is being driven by perceived lack of graduate job prospects, the rise in tuition fees and wage underpayment. We conclude that this may well fuel uncertainty and reduce demand for HE from lower socio-economic groups while increasing intra class conflict in higher socio-economic groups.